PENGARUH PENERAPAN MODEL PEMBELAJARAN NHT BERBANTUAN MEDIA ULAR TANGGA TERHADAP HASIL BELAJAR TATA SURYA DI SMP - Fauziah Nofrida; Stepanus Sahala Sitompul; Syaiful B. Arsyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine whether there is a difference in the learning outcomes of students who are given the application of the cooperative learning model type NHT assisted by snake and ladder media with students who are given the usual learning model on solar system material in class VII SMP Negeri 23 Pontianak and know the effect of cooperative learning type NHT assisted by snake and ladder media. The form of research used is quasy experimental design with a nonquivalent control groub design. The population in this study were students of class VII SMP Negeri 23 Pontianak. Data collection was done by using measurement techniques. The data collection tool was a learning outcome test in the form of an essay consisting of 15 questions with a reliability level of 0.42. Based on the results of posttest data analysis using the Mann Whitney U test with α = 5% Zhitung (-2.25) and Ztabel (1.96). The result of the effect size calculation is 0.79, which means that cooperative learning type NHT assisted by snake and ladder media has a high influence on student learning outcomes.Keywords: NHT, snake media, Solar System